Pengaruh Overconfidence, Herding Behavior, dan Loss Aversion terhadap Keputusan Investasi Generasi Z di Kota Denpasar - I Ketut Bagus Diasrahagi Putra; I Gusti Agung Ayu Pramita Indraswari (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2026)
This study aims to determine the influence of overconfidence, herding behavior, and loss aversion on investment decisions. The sample in this study is Generation Z with an age range of 18–28 years in Denpasar City who have made investments, with a total of 110 respondents. This study uses a quantitative approach with data collection techniques through questionnaires. The data analysis technique used is Partial Least Squares (PLS) version 4 to test the relationship between research variables. The results of the study show that overconfidence has a positive and significant effect on investment decisions, herding behavior also has a positive and significant effect on investment decisions, and loss aversion has a positive and significant effect on investment decisions. Based on the results of the study, researchers suggest that Generation Z in Denpasar City increase the intensity of evaluation and management of investment fund allocation, expand investment experience, improve investment literacy and knowledge, and conduct a more in-depth risk analysis so that investment decisions are more rational and optimal.